Association between somatic cell count after first parturition and cumulative milk yield in dairy cows - Archer, Simon C.; McCoy, Finola; Wapenaar, Wendela; Green, Martin J. (BMJ Publishing Group, 2013)
The aim was to assess the association between the somatic cell count of parity 1 cows between 5 and 30 days in milk (SCC1), and subsequent cumulative milk yield over approximately two years for cows in English and Welsh dairy herds. The dataset included records from 43,461 cows in 2111 herds, from 2004 to 2006. Cumulative milk yield was the model outcome, and a random effect was included to account for variation between herds. The model fitted the data well and was used to make predictions of cumulative milk yield, based on SCC1. A unit increase in the natural logarithm of SCC1/1000 was associated with a median decrease in cumulative milk yield of 482 kg, over a median study period of 868 days.